Kepemimpinan dan Manajemen Kepala sekolah - Eliana; Nurbismi; Nurliana; Syarifah Mauli Syitah; Indra Kesuma (JKA, 2024)
It is very important for the head of school to manage and oversee school activities to a goal. School leaders, in the growing era of digital technology, must also be able to integrate the principles of digital ethics into their curricula to form a responsible and ethical generation in the use of such technology. In addition, the head of the school must be able to motivate the teachers to behave well and provide guidance, coordination, activities, and supervision, as well as carry out the necessary supervision in the school management. School leaders must be able to manage school resources, incorporate digital ethics principles into the curriculum, motivate teachers, and carry out effective supervision and control. They also have to be innovators, leaders, honest, responsible, and able to make decisions. In this growing technology age, school leaders must be able to incorporate the principles of digital ethics into their curricula so that they can form a generation that uses technology well and responsibly. By doing these things, the head of the school can organize the school well so that the educational goals can be achieved.